2017
DOI: 10.15406/ijvv.2017.04.00079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hematological Bio Markers during Vaccination and Challenge of Brucella melitensis in Goats

Abstract: Brucella melitensis affects both animals and humans and causes severe economic losses mainly due to abortions, stillbirths and reproductive disorders in animals besides being potentially hazardous to the animal handlers. The losses can be prevented and controlled through the use of Rev.1 vaccine. The protective ability of Rev.1 against locally prevalent virulent strain and its ability to induce adaptive immune response involve cellular interactions depending upon pathophysiological changes and induction of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…This varies from the findings of Jo et al (2014), who observed an increase in total WCC following vaccination of indigenous goats. However, it agrees with Kumar et al (2017), who found no significant differences in total WCC but observed significant differences in monocyte counts. Furthermore, in agreement with Kumar et al (2017), monocyte counts significantly reduced following vaccination, this could have been due to a mild inflammation following vaccination.…”
Section: Advances In Animal and Veterinary Sciences March 2022 | Volu...supporting
confidence: 91%
See 2 more Smart Citations
“…This varies from the findings of Jo et al (2014), who observed an increase in total WCC following vaccination of indigenous goats. However, it agrees with Kumar et al (2017), who found no significant differences in total WCC but observed significant differences in monocyte counts. Furthermore, in agreement with Kumar et al (2017), monocyte counts significantly reduced following vaccination, this could have been due to a mild inflammation following vaccination.…”
Section: Advances In Animal and Veterinary Sciences March 2022 | Volu...supporting
confidence: 91%
“…However, it agrees with Kumar et al (2017), who found no significant differences in total WCC but observed significant differences in monocyte counts. Furthermore, in agreement with Kumar et al (2017), monocyte counts significantly reduced following vaccination, this could have been due to a mild inflammation following vaccination. Useh et al (2010), reported a significant decrease in monocyte count following blackleg infection, however, there was no significant difference in total WCC.…”
Section: Advances In Animal and Veterinary Sciences March 2022 | Volu...supporting
confidence: 91%
See 1 more Smart Citation
“…The prevention and control of B. melitensis in sheep and goats can be the best fitted model to control human brucellosis. For the purpose it is important to understand the patho-physiological interface involved in the course of disease in sheep or goats as virulence of Brucella species varies according to species, strain and the number of brucellae in inoculums [5,6]. Moreover, being intra cellular parasite, the pathogenic potential of Brucella spp.…”
Section: Introductionmentioning
confidence: 99%